Proteomics - S. Dolomatov; V. Kazakova; W. Zukow (Kazimierz Wielki University, 2021)
Proteomics is a branch of molecular biology that deals with the identification and quantification of proteins in living objects, as well as the analysis of protein functions and their interactions. Proteomics is studied by proteins that are expressed in a given cell, tissue or organism over a period of time (under certain conditions). It is known that information about the primary structure of a protein (the sequence of amino acid residues in a protein) is contained in a structural gene in the form of a codon sequence (genetic code). On the other hand, less than 10% of genes are functionally active (expressed) in the somatic cells of our body. Moreover, a distinct tissue-specific expression of genes is observed. This, in turn, leads to the peculiarities of the qualitative composition of the synthesized proteins in various tissues. No less important is the fact that the total amount of proteins synthesized by our tissues is much greater than the total number of structural genes containing information about their original structure. This phenomenon is explained by the activity of such mechanisms as alternative splicing and a wide variety of post-translational peptide processing pathways (covalent modification of a polypeptide synthesized on the ribosome) in health and disease. Thus, even a brief review of the semantic content of the term "proteomics" indicates an extremely complex system of protein molecules in our body, which plays a fundamental role in maintaining homeostasis and is involved in the formation of adaptive responses in response to adverse changes in the internal and external environment.